(untitled) (Bangladesh Journal of Neurosurgery, 2020)
A 55 year old female patient presented with progressive back pain of 6 month duration,aggravated on lying down, associated with weakness and numbness of the bothlower limbs for since 4 months. On neurological examination, the tone was foundincreased in both the lower limbs with a subjective power of grade 3/5 in both thelower limbs. Ankle and knee jerks were brisk with hypoaesthesia below D12dermatomes bilaterally, plantars were extensor. A clinical diagnosis of involvement ofD9 spinal level lesion was made. Magnetic resonance imaging (MRI) of the dorsolumbarspine showed an intraduralextramedullary ventrally placed lesion at the D8–D9 vertebral level with significant compression of the spinal cord [Figure 1, 2, 3]. Thelesion appeared hyperintense on T2W image with no contrast enhancement and withsignificant compression and shifting of the cord to the left. After preoperative routinehematological investigations, she underwent operation by laminectomy of D8–D9vertebrae and total excision of the cystic lesion was performed [Figure 4, 5]. Histologicalexamination revealed respiratory type pseudostratified ciliated columnar cells and apathological diagnosis of bronchogenic cyst was rendered [Figure 6]. The patient hadan uneventful postoperative period with subjective improvement of her symptomswith reduced spasticity & improvement of motor grade to 4/5 in both lower limbs. Bang. J Neurosurgery 2020; 9(2): 146-150